Synthetic Cells Engaged in Molecular Communication: An Opportunity for Modelling Shannon- and Semantic-Information in the Chemical Domain - Magarini, Maurizio; Stano, Pasquale (Frontiers in Communications and Networks, 2021)
In this Perspective article we intend to focus on the opportunity of modelling Shannon information and/or “semantic” information in the field originated by the convergence of bottom-up synthetic biology (in particular, the construction of “synthetic cells”) and the engineering approaches to molecular communication. In particular we will argue that the emerging technology of synthetic cell fabrication will allow novel opportunities to study nano-scale communication and manipulation of information in unprecedented manner. More specifically, we will discuss the possibility of enquiring on the transfer and manipulation of information in the chemical domain, and interpreting such a dynamics according to Shannon or to MacKay-Bateson (“semantic” information).